PREFERENCES IN PHYSICAL RECREATION OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS OF THE REPUBLIC OF ADYGEA - Kahuzheva, Z.K.; Panina, E.A.; Chuntyzheva, Z.I.; Kuprina, N.K. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify preferences in the physical recreation of students of universities of the Republic of Adygea. Methods and structure of the study. A set of scientific methods was used: analysis of scientific papers on the subject under consideration, online questioning, processing of the obtained information using the Statistica 12 software package, Microsoft Office Excel 2007, Yandex.Forms service, statistical processing method, graphical interpretation. The study was conducted with students of universities of the Republic of Adygea from October to December 2021. 3,400 students (58.6% women, 41.4% men) took part in it. The questionnaire contained questions aimed at identifying the basic indicators of the respondents’ choice of forms of physical recreation: factors, motives, criteria. Results and conclusions. The conducted research made it possible to accumulate information concerning the motives for students’ choice of forms of physical recreation, its preferred types, the specifics of the organization of active recreation, the dominant sources of information about sports and health-improving services and the criteria for consumer choice. The study revealed a fairly large group of respondents showing an increased interest in physical recreation, which confirms the success of the work on creating a positive image of sports, recreational and recreational activities among the youth.